Implementing the 7P Marketing Mix in Islamic Education: Insights from Phatnawitya School, Thailand - Isti Amalia N. Ibrahim; Muhammad Nuril Huda; Afida Safriani; Masitoh Luebaesa (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2023)
This research provides an in-depth examination of the 7P marketing mix strategy within Phatnawitya School, an Islamic institution catering to a minority Muslim community in a predominantly Buddhist region of Southern Thailand. Utilizing a qualitative methodology with a descriptive approach, the study explores the school's application of the 7P framework, focusing on the creation of well-rounded individuals and the establishment of a strong community presence. The collected data reveal a comprehensive education offering, from early childhood to advanced Islamic studies, facilitated by a robust infrastructure and innovative programs such as the Change ILP and sports initiatives. The school's approach to market identification, segmentation, and product differentiation demonstrates a strategic alignment with the needs and expectations of its student body. The research highlights the school's adept use of both direct community engagement and social media to communicate its values and offerings. While the study is limited by its singular focus on one institution, the findings suggest that Phatnawitya School's implementation of the marketing mix can inform broader strategies for Islamic educational services in similar socio-cultural contexts. Recommendations for further research include a broader examination of marketing strategies across Islamic educational institutions with varying cultural influences.